THE RELATIONSHIP BETWEEN NURSING CARING BEHAVIOR AND FAMILY ANXIETY IN THE INTENSIVE CARE UNIT - Widya Sepalanita; Nabila Fika Aprilia; Toto Subiakto; Lindawati; Nabella Ayu JF (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Background: Patients who are admitted to the ICU are patients with critical conditions; therefore, there is a higher level of anxiety in the patient's family. One of the efforts or roles of nurses to reduce anxiety in the families of ICU patients is to show caring behavior.   Caring behavior of nurses is an attitude of concern shown by health workers, especially nurses, towards patients and families. Family is the main support that is very important for the patient's recovery; if support is not obtained, it will affect the patient's healing process. One of the efforts or roles of nurses to reduce anxiety in the families of ICU patients is to show caring behavior. Objective: To determine the Relationship between the Caring Behavior of Nurses and Family Anxiety in the Intensive Care Unit of Dr. Dradjat Prawiranegara Hospital, Serang Regency. Methods: This study used a correlational analytical design of a cross-sectional approach. The research sample used purposive sampling with a total of 39 respondents. This research was carried out in the ICU of Dr. Drajat Prawiranegara Hospital in Serang Regency on March 8-24, 2024. The research instrument used a nurse caring behavior questionnaire based on a modified CBA and a HARS anxiety level questionnaire. Research Results: The results of the study showed that there was a relationship between nurses' caring behavior and ICU family anxiety.